IMPACT OF DEMONETIZATION ON INDIAN BANKING STOCKS: AN EVENT STUDY METHODOLOGY - Raut, Rajesh; Thorve, Harsha; Owhal, Shrawan (Indian Journal of Finance and Banking, 2021)
Demonetization is the withdrawal of a particular form of currency from circulation. In other words, the notes lose their value as a currency. It is an instrument that is used to manage various economic problems such as inflation, corruption, tax evasion, etc. The Indian government on November 8, 2016, decided to demonetize high denomination currencies. This announcement had an impact on several sectors of the Indian economy. This study is an investigation to measure the impact of demonetization announcements on the Indian banking sector. This study employs cumulative abnormal return (CAR) and an event study methodology to measure the impact of the decision on the selected banking stocks. The study shows that demonetization had a significant impact on the stock prices of selected banks. The findings of the study suggest that on the event day, none of the selected stock has shown significant positive abnormal returns. Further on the event day and followed by the event day positive significant ARR is observed indicating demonetization had a significant impact on the stock prices of selected banks. Also, CAR on the event day is not equal to zero indicating the Indian stock market was not efficient for demonetization announcement.JEL Classification Codes: G10, G14, G18, G21.